Prevalence and Predictors of Pulmonary Embolism in Hospitalized Patients with Syncope. Issue 8 (August 2019) - Ammar, Hussam; Ohri, Chaand; Hajouli, Said; Kulkarni, Shaunak; Tefera, Eshetu; Fouda, Ragai; Govindu, Rukma
Abstract : Objectives: Approximately one in six patients hospitalized with syncope have pulmonary embolism (PE), according to the PE in Syncope Italian Trial study. Subsequent studies using administrative data have reported a PE prevalence of <3%. The aim of the study was to determine the prevalence and predictors of PE in hospitalized patients with syncope. Methods: We retrospectively reviewed the records of patients who were hospitalized in the MedStar Washington Hospital Center between May 1, 2015 and June 30, 2017 with deep venous thrombosis, PE, and syncope. Only patients who presented to the emergency department with syncope were included in the final analysis. PE was diagnosed by either positive computed tomographic angiography or a high-probability ventilation-perfusion scan. Univariate and multivariate logistic regressions were used to assess the associations between clinical variables and the diagnosis of PE in patients with syncope. Results: Of the 408 patients hospitalized with syncope (mean age, 67.5 years; 51% men [N = 208]), 25 (6%) had a diagnosis of PE. Elevated troponin levels (odds ratio 6.6, 95% confidence interval 1.9–22.9) and a dilated right ventricle on echocardiogram (odds ratio 6.9, 95% confidence interval 2.0–23.6) were independently associated with the diagnosis of PE. Age, active cancer, and history of deep venous thrombosis were not associated with the diagnosis of PE. Conclusions: The prevalence of PE in this study is approximately one-third of the reported prevalence in the PE in Syncope Italian Trial study and almost three times the value reported in administrative data-based studies. PE should be suspected in patients with syncope and elevated troponin levels or a dilated right ventricle on echocardiogram. Abstract : Approximately 1 in 6 patients hospitalized with syncope will have pulmonary embolism (PE), according to the PE in Syncope Italian Trial (PESIT) study. Subsequent studies using administrative data have reported a PE prevalence of <3%. The aim of the study was to determine the prevalence and predictors of PE in hospitalized patients with syncope. The authors retrospectively reviewed the records of patients who were hospitalized in the MedStar Washington Hospital Center with deep venous thrombosis, PE, and syncope. Only patients who presented to the emergency department with syncope were included in the final analysis. Univariate and multivariate logistic regression were used to assess the associations between clinical variables and the diagnosis of PE in patients with syncope.